Barriers to evidence-based practice implementation in physiotherapy: a systematic review and meta-analysis. (26th June 2021) - Paci, Matteo; Faedda, Gianni; Ugolini, Alessandro; Pellicciari, Leonardo
Abstract: Background: To review and meta-analyse the evidence about the prevalence of barriers to evidence-based practice (EBP) reported in physiotherapy. Methods: Two independent investigators conducted an extensive electronic search in EMBASE, PubMed, Scopus, Web of Science and CINAHL databases from their inception to July 2020 and included the retrieved articles if they investigated barriers to EBP among physiotherapy professionals. Subsequently, they extracted data and assessed the methodological quality using a scale described in a similar previous study. The outcome for meta-analysis was frequency of each reported barrier. Sub-analyses were performed grouping studies based on countries where surveys were performed, classified as either developed or developing countries. Results: Twenty-nine articles were included in the systematic reviews and meta-analysis. Risk of bias assessment of included studies showed a median score: 4 points (interquartile range: 3–4). The findings of meta-analysis revealed that lack of time was the most frequently reported barrier (53.0% [95% confidence interval, 95%CI, 44.0–62.0]), followed by language (36.0% [95%CI 16.0–62.0]), lack of access (34.0% [95%CI 23.0.27]) and lack of statistical skills (31.0% [95%CI 20.0–44.0]). Lack of skills and lack of generalizability were declared as barriers by 27.0% [95%CI 18.0–38.0] and 23.0% [95%CI 15.0–33.0] of responders, respectively. Lack of support and lack of interest are less frequent, with 16.0% [95%CI 11.0–24.0] and 9.0% [95%CI 6.0–15.0] of responses, respectively. Barriers reported in investigations performed in developed countries were less frequent when compared to those performed in developing countries. Conclusion: Organizational issues and methodological skills seem key issues to allow the implementation of EBP, suggesting the need to adopt or enhance organizational and training strategies to facilitate the implementation of the EBP. Quantitative synthesis showed high heterogeneity for all analyses, and therefore, pooled data should be interpreted with caution.